The Role of Service Feature Dimensions to Drive Purchase Decisions and Loyalty (Analysis of Go-Food Consumers in Makassar) - R Reynilda; Azlan Azhari; M Maryadi (Fakultas Ekonomi, Universitas Bangka Belitung, 2023)
This study aims to analyze the role of service feature dimensions on purchasing decisions and then their impact on consumer loyalty using GoFood. The approach used in this research is a quantitative approach. The population in this study are all consumers who have used the GoFood application in Makassar City. The number of samples used was 120 respondents with accidental sampling technique. Data collection in this study was a survey method with research instruments using questionnaires distributed using the Google form. The data collected was then analyzed using Smart PLS. The results of the study show that directly the service feature dimensions are Feature Completeness, Ease of Features and Feature Suitability have a positive and significant effect on Purchase Decision. Furthermore, the variables Completeness of Features, Ease of Features, Suitability of Features and Purchase Decision directly have a positive and significant effect on Consumer Loyalty. As well as the Purchase Decision variable can mediate the indirect relationship between the Completeness of Features, Ease of Features and Feature Suitability to Consumer Loyalty.